Epidemiology of alopecia areata in Baqubah city/Diyala-Iraq - Shihab Ahmed, Rihab; Ahmed Shakir, Shahab; Saleh Mahdi, Ahmed; Ghazal Noaman, Nadhim (Diyala Journal of Medicine, 2023)
Background: Alopecia areata is a disease scalp and body hair leading to patches of non-scoring alopecia which is heterogeyous ,it is unown as autommutte disease, there is no prevention & hard cure. Objective: To determine the prevalence rate according to sex &age and the causative factors of alopecia areata in Baquba city. Patients and Methods: A cross-sectional study was in Baquba Teaching Hospital dermatological clinic from 1st of October 2020 to 31st of March 2022 at Baquabah teaching Hospital /outpatient Dermatology clinic. The study sample (100) patients with different clinical variants of Alopecia Areata, (71) males and (29) females of different age groups. Results: This study shows that high prevalence among males (71%) with age group (21-30) years old with single patchy alopecia areata with past history of recurrence and associated psychological history. (100) cases of AA were diagnosed. (25%). Single lesion of AA was the most common manifestation (68%). Recurrence history of AA Positive in (55%). Personal history of stress was associated with AA in (64 %). The most common site of alopecia areata was in head (55%). Conclusion: It was concluded that, alopecia areata was more common in male, age (21-30) years, most common single lesion, more in head, with psychological stress history.